THE PRINCIPLES OF LANGUAGE TEACHING - Meli Damayanti (Politeknik Negeri Sriwijaya, 2022)
Learning a language is learning to communicate through that language. Therefore, language teaching is directed to improve communicative skills in various communication contexts. The abilities developed are the ability to grasp meaning, role, interpret, assess, and express oneself through the use of language. All of them are grouped into language skills, understanding, and use. To achieve these teaching goals, language teaching must pay attention to the principles of language learning, and then implement these principles into various learning activities. Language teaching requires settings related to software such as knowledge of the nature of language, learning theory, and about the characteristics of people who will learn the language. In essence, teaching a language, whether it is a first language, a second language, or a foreign language, is an activity that does not stand alone, but requires the services of other relevant sciences. There are two theoretical foundations in the development of language teaching, namely the theory of psychology (Psychology) and linguistics (Linguistics). This paper will discuss the 12 principles of language teaching proposed by Brown. These principles relate to cognitive, affective, and linguistic aspects. Keywords: the principles, language teaching